keeping in mind that anything raised at the 0 power, is 1, with the sole exception of 0 itself.
![\bf ~~~~~~~~~~~~\textit{negative exponents} \\\\ a^{-n} \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^{-n} \qquad \qquad a^n\implies \cfrac{1}{a^{-n}} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{(r^{-7}b^{-8})^0}{t^{-4}w}\implies \cfrac{1}{t^{-4}w}\implies \cfrac{1}{t^{-4}}\cdot \cfrac{1}{w}\implies t^4\cdot \cfrac{1}{w}\implies \cfrac{t^4}{w}](https://tex.z-dn.net/?f=%20%5Cbf%20~~~~~~~~~~~~%5Ctextit%7Bnegative%20exponents%7D%0A%5C%5C%5C%5C%0Aa%5E%7B-n%7D%20%5Cimplies%20%5Ccfrac%7B1%7D%7Ba%5En%7D%0A%5Cqquad%20%5Cqquad%0A%5Ccfrac%7B1%7D%7Ba%5En%7D%5Cimplies%20a%5E%7B-n%7D%0A%5Cqquad%20%5Cqquad%20a%5En%5Cimplies%20%5Ccfrac%7B1%7D%7Ba%5E%7B-n%7D%7D%0A%5C%5C%5C%5C%5B-0.35em%5D%0A%5Crule%7B34em%7D%7B0.25pt%7D%5C%5C%5C%5C%0A%5Ccfrac%7B%28r%5E%7B-7%7Db%5E%7B-8%7D%29%5E0%7D%7Bt%5E%7B-4%7Dw%7D%5Cimplies%20%5Ccfrac%7B1%7D%7Bt%5E%7B-4%7Dw%7D%5Cimplies%20%5Ccfrac%7B1%7D%7Bt%5E%7B-4%7D%7D%5Ccdot%20%5Ccfrac%7B1%7D%7Bw%7D%5Cimplies%20t%5E4%5Ccdot%20%5Ccfrac%7B1%7D%7Bw%7D%5Cimplies%20%5Ccfrac%7Bt%5E4%7D%7Bw%7D%20)
- x intercept=a=3
- y intercept=b=-2
We need the normal form first
![\\ \rm\bull\rightarrowtail \dfrac{x}{a}+\dfrac{y}{b}=1](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5Cbull%5Crightarrowtail%20%5Cdfrac%7Bx%7D%7Ba%7D%2B%5Cdfrac%7By%7D%7Bb%7D%3D1)
![\\ \rm\bull\rightarrowtail \dfrac{x}{3}-\dfrac{y}{2}=1](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5Cbull%5Crightarrowtail%20%5Cdfrac%7Bx%7D%7B3%7D-%5Cdfrac%7By%7D%7B2%7D%3D1)
Multiply by 6to bring standard form
![\\ \rm\bull\rightarrowtail 2x-3y=1](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5Cbull%5Crightarrowtail%202x-3y%3D1)
Answer:
![3*(2x+3)*(x+1)](https://tex.z-dn.net/?f=3%2A%282x%2B3%29%2A%28x%2B1%29)
Step-by-step explanation:
pull like terms from the problem to re-arrange it into a product
![\left(2x+3\right)\left(3x+3\right)\\3x + 3 = 3 \cdot (x + 1)\\3 \cdot (2x + 3) \cdot (x + 1)\\](https://tex.z-dn.net/?f=%5Cleft%282x%2B3%5Cright%29%5Cleft%283x%2B3%5Cright%29%5C%5C3x%20%2B%203%20%20%3D%20%20%203%20%5Ccdot%20%28x%20%2B%201%29%5C%5C3%20%5Ccdot%20%282x%20%2B%203%29%20%5Ccdot%20%28x%20%2B%201%29%5C%5C)
answer: I think the result is 12
Step-by-step explanation:
c(b+a)-a=
2(3+6)-6=
6+12-6= 12